Assessment of parental attitude toward different behavior management techniques used in pediatric dentistry - Sneha Pramod Desai; Preetam P Shah; Shweta S Jajoo; Patil S Smita (Wolters Kluwer Medknow Publications, 2019)
Background: The goal of any good dental treatment is to provide a quality dental care to the patient. This may not be possible if the patient is unwilling to cooperate or unable to do so due to their age or related factors. In such children, behavior management techniques are very helpful. With changing times, there have been changes in the law and the outlook of parents and society toward dental treatment. This influences the various behavior management methods used by pediatric dentists. Objectives: This study was conducted to assess the attitudes of parents of children of different pediatric age groups towards: Behavior management techniques used by pediatric dentists The effect of maternal anxiety on the child's behavior in clinic Pharmacological behavior management techniques The effect of parental presence in the operatory on the child's behavior. Materials and Methods: Three hundred parents were evaluated and divided into three groups comprising 100 each on the basis of their children's age, Group A: 2-5 years, Group B: 6-9 years, and Group C: 10-13 years, which were further divided into two subgroups, on the basis of the child's gender, with each subgroup having parents of 50 male and 50 female children each. For example, Group A1: 50 parents of 2-5-year-old boys, Group A2: 50 parents of 2-5-year-old girls. Results: ANOVA test showed different hierarchies of acceptance for the techniques in all the groups. In all the three groups, tell show do, positive reinforcement, and live modeling were the most accepted techniques. However, statistically significant difference between the groups was not observed for the three techniques. The least accepted techniques for all the groups were hand over mouth technique and voice control technique. Conclusion: Parents were more receptive of those techniques which were visually more acceptable involving a communicative management, such as tell show do, positive reinforcement, and live modeling.